Investment attractiveness factors in the opinion of companies from Special Economic Zones in Poland - Piotr Misztal; Vasili Kulakou (Managerial Economics)
The purpose of the research is the identification of important determinants shaping the investment attractiveness of the country (region) from the point of view of potential investors and an assessment of the degree of stakeholder satisfaction with existing methods of examining the investment climate and their availability for practical use. In order to assess a set of determinants that exert the most significant influence on a country’s investment climate, a questionnaire was developed consisting of 25 questions of various orientations. These questions were designed to assess the opinions of potential investors regarding the degree of influence of various factors on their decision on capital allocation and the investment climate of a country. The survey was conducted among 506 enterprises and 14 management bodies of Special Economic Zones in Poland from June 10 to July 20, 2023. The final step involved the analysis of the survey results using statistical methods.